2010
DOI: 10.1007/s11738-010-0536-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of seed viability in maize

Abstract: To identify specific proteins related to maize seed viability, seeds of Zhengdan 958 (one of the highyield maize hybrids in China) were sorted based on viability evaluation with triphenyltetrazolium chloride (TTC) assay and used for comparative proteomic analysis. After TTC staining, embryos of high-viability seeds were deep red (R type), while embryos of dead seeds were white (W type). Proteomic analysis revealed that 28 protein spots identified were differently expressed significantly between R and W embryos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 45 publications
2
52
0
2
Order By: Relevance
“…With regard to that overexpression of gliceraldehyd-3-phosphate-dechydrogenase observed by us was also mentioned by other authors (Gallardo et al 2001;Catusse et al 2011;Wu et al 2011), however, other glycolytic or Krebs cycle enzymes indicated as vigour markers were different depending on the seed type. In addition, Catusse et al (2011) also pointed to the voltage-dependent anion channels (VDACs) as these markers, which were confirmed neither by other authors nor by us.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…With regard to that overexpression of gliceraldehyd-3-phosphate-dechydrogenase observed by us was also mentioned by other authors (Gallardo et al 2001;Catusse et al 2011;Wu et al 2011), however, other glycolytic or Krebs cycle enzymes indicated as vigour markers were different depending on the seed type. In addition, Catusse et al (2011) also pointed to the voltage-dependent anion channels (VDACs) as these markers, which were confirmed neither by other authors nor by us.…”
Section: Resultssupporting
confidence: 77%
“…The seed variants: nt and H, were the reference for the detection of melatonin-associated proteins, since it is well known that already the conditioning with water provokes modifications in seed proteome (Catusse et al 2011;Wu et al 2011;Gallardo et al 2001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Essas são proteínas de choque térmico, que são responsáveis pela estabilização da conformação de outras proteínas e estão associadas à viabilidade das sementes durante a maturação e o armazenamento, além de protegerem outras moléculas durante a secagem, o que confere tolerância à dessecação (Wu et al, 2011).…”
Section: Resultsunclassified